Common aspects of the Chicago and Harvard schools of antitrust analysis: The neo-institutional contribution [Aspectos comunes de las escuelas de Chicago y Harvard en materia de libre competencia: El aporte del neoinstitucionalismo] (2019)
On the understanding that Harvard and Chicago Schools postulates, this paper conducts a comparative analysis between those and the conceptual pillars of the Neo-institutional School. Within the framework of traditional disputes between Chicago and Harvard Schools, the advances of neoinstitutionalism, might explain how both Schools support different purposes for competition law, but rely on the same origins, since the two of them were created to fight harmful excess of market power and corporate mergers. It is in that context, the neoinstitutionalism explains how processes of market power and concentration can emerge, going beyond what traditional perspectives have considered about them. © 2019, Universidad Nacional Autonoma de Mexico. All rights reserved.